PENGARUH BIAYA LINGKUNGAN, KEPEMILIKAN SAHAM MANAJEMEN, DAN PENGAWASAN RISIKO TERHADAP RASIO PENGEMBALIAN EKUITAS SERTA PENGARUHNYA TERHADAP HARGA SAHAM - Permana Putra Lesmana; Juniati Gunawan (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This research aims to analyze the effect of environmental cost, managerial ownership, risk oversight on return on equity and its effect on share price. The main reason this research is conducted is due to the result of CFA institute survey in 2020 that mainly said 85% of respondent using the environment, social, and governmental factors into investment decision. The survey concluded that the existence of company in the long term is not only for the profit purposes, but also has the responsibility to preserve the environment and social. 126 sampels has been analyzed using the purposive sampling method. The sampels consist of the processing industry based on KBLI 2020 that listed on Indonesia Stock Exchange during 2018-2020 period. Financial statements, annual report, and sustainability report are used to analyze the variables with structural equation modeling-partial least square (SEM PLS). The results show that environmental cost has a positive and significant effect on return on equity, managerial ownership has a negative and significant effect on return on equity, return on equity has a positive and significant effect on share price, and ratio on equity are able to mediate the effect of environmental cost and managerial ownership on share price.